2014
DOI: 10.1016/j.neuroimage.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Why diffusion tensor MRI does well only some of the time: Variance and covariance of white matter tissue microstructure attributes in the living human brain

Abstract: Fundamental to increasing our understanding of the role of white matter microstructure in normal/abnormal function in the living human is the development of MR-based metrics that provide increased specificity to distinct attributes of the white matter (e.g., local fibre architecture, axon morphology, and myelin content). In recent years, different approaches have been developed to enhance this specificity, and the Tractometry framework was introduced to combine the resulting multi-parametric data for a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
234
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 233 publications
(263 citation statements)
references
References 48 publications
22
234
2
Order By: Relevance
“…Whereas HMOA represents a surrogate of tissue density (tissue microstructure) (Dell'Acqua et al, 2013), the track volume, which is calculated as the number of voxels intersected by the reconstructed streamlines, denotes the space occupied by the tract (macrostructure) and its relationship to axonal number, axonal diameter, and density has yet to be established (Beaulieu, 2002). The findings that HMOA and tract volume differentially contribute to the anatomical lateralization of frontoparietal attentional networks are in agreement with previous studies showing that the asymmetry of WM pathways varies across different measures derived from diffusion MRI (De Santis et al, 2014). A remaining question, which cannot be answered by the current study, is whether variability in WM organization and in structural lateralization is reflected in individual differences in functional connectivity and/or preferential right hemisphere activation during visuospatial attention tasks.…”
Section: Lateralization Of Frontoparietal Networksupporting
confidence: 86%
“…Whereas HMOA represents a surrogate of tissue density (tissue microstructure) (Dell'Acqua et al, 2013), the track volume, which is calculated as the number of voxels intersected by the reconstructed streamlines, denotes the space occupied by the tract (macrostructure) and its relationship to axonal number, axonal diameter, and density has yet to be established (Beaulieu, 2002). The findings that HMOA and tract volume differentially contribute to the anatomical lateralization of frontoparietal attentional networks are in agreement with previous studies showing that the asymmetry of WM pathways varies across different measures derived from diffusion MRI (De Santis et al, 2014). A remaining question, which cannot be answered by the current study, is whether variability in WM organization and in structural lateralization is reflected in individual differences in functional connectivity and/or preferential right hemisphere activation during visuospatial attention tasks.…”
Section: Lateralization Of Frontoparietal Networksupporting
confidence: 86%
“…Group differences in FA occurred in a smaller subset of white matter tracts. This pattern of findings is generally consistent with empirical evidence demonstrating that larger sample sizes may be required for observing significant group differences with FA than with quantitative T1 (R1 = 1/T1) measures (De Santis et al, 2014). In the same study, De Santis et al (2014) also found that FA, T1, and a separate measure of myelin water fraction (MWF), were most strongly correlated in tract regions comprised of single fiber populations but were not correlated in regions comprised of multiple fiber populations.…”
Section: Group Differences In R1supporting
confidence: 84%
“…The lack of significant FA differences within these pathways and other tracts may be explained by limitations of diffusion-based methods for identifying group differences in FA in small sample sizes or by possible differences between adolescent and adult study populations. Empirical work performed by De Santis and colleagues has estimated that group sizes involving 20 to 30 participants are necessary for observing group FA differences within inferior fronto-occipital fasciculus or cingulate pathways (De Santis et al, 2014). These estimates are comparable to a previous dMRI study of AN in which significant FA differences were observed for these pathways (Frieling et al, 2012).…”
Section: Tablesupporting
confidence: 55%
See 2 more Smart Citations